EDUKASI TENTANG PENTINGNYA KECERDASAN SPIRITUAL BAGI ANAK USIA 5-13 TAHUN DI DESA JANJANG - Sisi Sisi (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
This PkM activity was carried out in Janjang Village, Tayan Hulu District, West Kalimantan. The approaches used are field surveys and literature research. The PkM activities held were an effort to provide training to children aged 5-13 years in Janjang Village about the urgency of spiritual intelligence. The implementation of the service activities was motivated by the fact that some children in Janjang Village were experiencing degradation in their spiritual intelligence, so this had a significant impact on their spiritual life and morality which was not in accordance with the truth of God's Word. Looking at this problem, the PkM Service offered an idea as an alternative solution to the problem, namely: Providing education to children aged 5-13 years in Janjang Village about the meaning, benefits and indicators of spiritual intelligence that must be known, understood and manifested. The results obtained from this PkM activity are that children aged 5-13 years in Janjang Village already understand and comprehend the meaning, benefits and indicators of spiritual intelligence, as well as how to apply them in their lives.